Strategi Komunikasi Pemasaran Minuman Tradisional Moke sebagai Identitas Budaya Kota Kupang - Anggreswari, Ni Putu Yunita; Melo, Chelo Alcina Carlota Alves de (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the marketing communication strategies of the traditional beverage Moke as a representation of the cultural identity of the people of Kupang City. Moke is not only regarded as a consumable product but also as a symbol of social values, togetherness, and cultural heritage passed down across generations. Using a descriptive qualitative approach, the study examines how communication strategies, both through traditional and digital media, can transform the image of Moke from a mere traditional drink into a local cultural icon. Data were collected through interviews, observations, and documentation. The findings indicate that the marketing communication strategy for Moke involves three main dimensions: first, the use of digital media to reach younger generations and expand the market; second, the utilization of traditional media and community interactions to maintain cultural legitimacy; and third, cultural narratives that emphasize the values of togetherness, tradition, and pride in local identity. However, the marketing of Moke also faces challenges in the form of negative stigma as an alcoholic beverage and limited government support in terms of regulation and promotion. In conclusion, marketing communication strategies play a crucial role not only in strengthening the image of Moke as a local product but also in preserving the cultural identity of Kupang City.